2018
DOI: 10.1088/1361-6455/aaf0b7
|View full text |Cite
|
Sign up to set email alerts
|

Polarization attack on continuous-variable quantum key distribution

Abstract: The shot-noise unit (SNU) is a crucial factor for the practical security of a continuous-variable quantum key distribution system. In the most widely used experimental scheme, the SNU should be calibrated first and acts as a constant during the key distribution. However, the SNU of a practical system is dependent on the various parameters of the local oscillator, which can be controlled by the eavesdropper in the open channel. In this paper, we report a quantum hacking method to control the practical SNU by us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…However, they found that by adding a third attenuation value (rather than just on or off) to the strong attenuation could prevent their attack. Xie et al [553] also found that a jitter effect in the clock signal can lead to an incorrect calculation of the shot noise, and Zhao et al [554] identified a polarization attack where the eavesdropper attacks unmeasured LO pulses to control and tamper with the shot-noise unit of the protocol.…”
Section: Attacks On the Local Oscillatormentioning
confidence: 99%
“…However, they found that by adding a third attenuation value (rather than just on or off) to the strong attenuation could prevent their attack. Xie et al [553] also found that a jitter effect in the clock signal can lead to an incorrect calculation of the shot noise, and Zhao et al [554] identified a polarization attack where the eavesdropper attacks unmeasured LO pulses to control and tamper with the shot-noise unit of the protocol.…”
Section: Attacks On the Local Oscillatormentioning
confidence: 99%
“…It is furthermore worth noting that even though the local estimator plays an important role during homodyne measurements, we did not include it in our analysis as this is rather a technical issue and can even be avoided. Similarly to our signal, the local oscillator is also subject to fluctuations and it also has to be estimated [41], but its estimation is considerably easier due to its high power and the fact that we only need to know its intensity. So the normalization of the local oscillator can be performed with high precision.…”
Section: The Modelmentioning
confidence: 99%
“…When implemented over standard optical fibres, one such noise source is random polarization drift in the communication channel, which will degrade the efficiency of the coherent detection scheme [3]. Therefore a polarization drift compensation scheme is strictly necessary for the implementation of efficient and secure CV-QKD systems [2,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%